Downregulation of delta‐aminolevulinate dehydratase is associated with poor prognosis in patients with breast cancer. Issue 4 (12th April 2017) - Ge, Jie; Yu, Yue; Xin, Fei; Yang, Zheng‐Jun; Zhao, Hong‐Meng; Wang, Xin; Tong, Zhong‐Sheng; Cao, Xu‐Chen
Abstract : Delta‐aminolevulinate dehydratase (ALAD) catalyzes the second step in the biosynthesis of heme and is also an endogenous inhibitor of the 26S proteasome. The role of ALAD in breast cancer progression is still unclear. In this study, we found that the expression of ALAD was downregulated in breast cancer tissues compared with adjacent normal breast tissues. Enhanced ALAD expression was associated with a favorable outcome in patients with breast cancer. Overexpression of ALAD suppresses breast cancer cell proliferation and invasion and inhibits the epithelial–mesenchymal transition phenotype. Furthermore, we found that ALAD regulates transforming growth factor‐β‐mediated breast cancer progression. This finding suggests that ALAD might be a potential biomarker for breast cancer that suppresses breast cancer progression by regulating transforming growth factor‐β‐mediated epithelial–mesenchymal transition. Abstract : ALAD is down‐regulated in breast cancer. ALAD inhibits breast cancer progression. ALAD regulates TGF‐β‐mediated EMT.